KARYA GRAFIS DENGAN OBJEK PETANI KELAPA - WIDIA NOVELA, Dr. Budiwirman, M.Pd., Drs. Ariusmedi. M.Sn. (Universitas Negeri Padang, 2019)
This final work aims to visualize coconut farmers in graphic works. Privileges in coconut farmers teach humans that humans will be useful in their environment if they have a value of responsibility, social values and are serious about doing everything. In this work one technique uses the stencil print technique. The method of the process of creating this work is: the stages of preparation, elaboration, synthesis, realization of concepts, and completion.The results of the work are made of 10 pictures with the title: Nurseries, Planting Seeds, Maintenance, Fruit Picking, Embroidering, Splitting Coconut, Drying, Prying Coconut, Collecting Coconut, and Selling. This final work is expected to be able to arouse the enthusiasm of the employee in creating more interesting graphics in the future.Kata kunci: petani kelapa, seni grafis